Design and Application of Energy Recovery System for AC Diesel Engine Test Platform - WU Tong; ZHOU You; NIU Jianna (机车电传动)
The diesel engine of AC diesel locomotive would generate huge of electricity energy during the maintenance and commissioning process. In order to recover those energy, the energy storage and novel power electronics topology based energy recovering system was developed. Project background was introduced, and the system function and working mode were analyzed. Design strategy and highlights of power conversion system, battery system and control and monitoring system was discussed. The simulation and test result demonstrated the validation and correctness of system design and demo development.